Chronic exposure of betaTC-6 cells to supraphysiologic concentrations of glucose decreases binding of the RIPE3b1 insulin gene transcription activator. - Poitout, V (1996)
We have shown previously that chronic exposure of HIT-T15 cells to supraphysiologic glucose concentrations causes decreased insulin gene transcription and decreased binding activities of two beta-cell specific transcription factors, STF-1 and the RIPE3b1 activator, and have suggested that these events may provide a mechanism for glucose toxicity on beta-cell function. However, this contention can be criticized because it is not clear whether these observations are unique to the HIT-T15 cell or generalizable to other beta-cell lines and the islet. Therefore, we cultured betaTC-6 cells for up to 41 wk in either 11.1 or 0.8 mM glucose. We observed a passage-dependent decrease in insulin content and insulin mRNA levels in betaTC-6 cells chronically cultured in 11.1 mM glucose. Cells chronically cultured in 0.8 mM glucose had higher insulin mRNA levels than cells chronically cultured in 11.1 mM glucose. The relative activity of a chloramphenicol acetyl transferase (CAT) reporter gene controlled by the 5' regulatory region of the human insulin gene was decreased in late passage betaTC-6 cells chronically cultured in 11.1 mM glucose, but was preserved in late passages of cells chronically cultured in 0.8 mM glucose. Electromobility shift assays demonstrated that binding of a specific nuclear protein that recognizes the RIPE3b1 binding site of the insulin gene was markedly diminished in late passage cells chronically exposed to 11.1 mM glucose, whereas binding activities of STF-1 and ICE activators were unchanged. RIPE3b1 binding activity was preserved in late passage cells chronically exposed to 0.8 mM glucose. Mutation of the RIPE3b1 binding site almost completely abolished insulin gene transcription as well as binding activity. We conclude that chronic exposure of betaTC-6 cells to high glucose concentrations paradoxically decreases insulin gene transcription, in part, by decreasing activity of the trans-activating factor which binds to the RIPE3b1 sequence. This study uniquely demonstrates that altered binding to the RIPE3b1 sequence mediates glucose toxicity in betaTC-6 cells, thus reinforcing the importance of this cis-acting element in the regulation of insulin gene transcription. We conclude that the phenomenon of glucose toxicity decreasing binding of transcription factors and thereby reducing insulin gene expression is not a feature solely of HIT-T15 cells and may be demonstrable generally in beta-cell lines.